Implementasi Socket Programming dalam Pembuatan Sistem Antrian - Amin, M. Miftakul (IIB Darmajaya, 2010)
Customer satisfaction is one aspect to be achieved by organizations that provide services to customers. One of the existing service is a queuing system which is the front guard in the process of service. Many public service organizations that have not applied the queuing system in the service. This resulted in a buildup of the queue and the calling process is still done conventionally. On the other hand queuing system that is much used in the form of hardware that if one day there is a change in the installation then the entire device must be replaced. Another alternative is a queuing system made with software that contains multimedia features. Making it easier for the installation and modification to the changes that occur. With the help of socket programming allows to send messages between computers connected in a queuing system, as well as additional multimedia features will further provide information of interest to the customer. Keyword: queuing system